Breathing fire : female inmate firefighters on the front lines of California's wildfires - Lowe, Jaime, 1976- (MCD / Farrar, Straus and Giroux, 2021)
"A dramatic, revelatory account of the female inmate firefighters who battle California's wildfires"--